Analysis of Traffic Performance Without Signals (Case Study of the Intersection of Jalan Pangeran Antasari-Sumber and Jalan Mertabasah, Cirebon Regency) - Abdi Sembada; Yusra Aulia Sari (LEADER: Civil Engineering and Architecture Journal, 2025)
Cirebon Regency is a Level II area that has experienced quite rapid traffic growth. Jalan Pangeran Antasari is one of the main roads in Cirebon Regency as a link between districts and is also a road with a fairly dense industrial area. An analysis of the intersection's performance is essential to maintain the level of road service. This paper aims to analyze traffic performance at intersections without signals. The research method was surveying Jalan Pangeran Antasari-Sumber and Jalan Mertabasah, Cirebon Regency, in November 2024—data analysis using the Indonesian Road Capacity Guidelines 2023. The research results on the performance of road sections and intersections indicate the value of vehicle volume obtained. The volume of traffic flow during peak hours on Jalan Pangeran Antasari is 1979 veh/hour or 1534,8 pcu/hour on Monday afternoon. The traffic volume at the unsignalized intersection of Jalan Pangeran Antasari-Sumber – Jalan Mertabasah during peak hours is 2763 veh/hour atau 1647,2 pcu/hour on Monday afternoon. The conclusion is that the capacity level of Jalan Pangeran Antasari was obtained at C = 3640 pcu/hour, Dj = 0,43, and then (LOS) with level B means good. The capacity value of the unsignalized intersection of Jalan Pangeran Antasari-Sumber – Jalan Mertabasah was obtained C= 1647,5 pcu/hour, q= 1643,2 pcu/hour, Degree of Saturation = 0,99 dan Delays at Intersections T= 17,99 sec/drive as well as queue opportunities 39,3% - 77,8%. Thus, the intersection service level obtains Level Of Service E, which means Bad.